Numerical study of an Evacuated Tube Solar Collector incorporating a Nano-PCM as a latent heat storage system. (April 2021) - Elarem, Raja; Alqahtani, Talal; Mellouli, Sofiene; Aich, Walid; Ben Khedher, Nidhal; Kolsi, Lioua; Jemni, Abdelmajid
Abstract: A new Evacuated Tube Solar Collector (ETSC) incorporating a Nano-PCM with fins is presented and studied. The numerical mathematical 2D model of phase change heat transfer is highlighted. The effect of adding nanoparticles of copper (Cu) to paraffin wax on system performance was investigated. The heat transfer during the energy storage process is simulated using the Ansys-Fluent. Moreover, the solid-liquid phase change characteristics of the paraffin within the system are analyzed. Additionally, an optimization analysis of fin parameters (i.e. fin thickness and fin spacing) is performed. Finally, a series of comparative simulations are carried out to investigate the performance of the ETSC system with and without the Solar Parabolic Trough Reflector (SPTR). The results showed that adding fins has a great effect on the phase change heat transfer of the paraffin in the ETSC. It was noted that the PCM melts faster as the thickness of the fins gets thinner. Also, the addition of 1% of Cu to the PCM was found to be the optimum mass concentration at which the HTF outlet temperature increased by 2 K. Moreover, it was found that the ultimate flow rate that caused the entire mass of the PCM to melt is 0.003 kg/s.